Magyar kikötőváros a térben : Fiume és földrajzi funkciói - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2013)
A special factor of the spatial history of the Hungarian state is its former seaport of Fiume, which used to be the gateway of the Kingdom of Hungary to the Adriatic from the time of the Austro-Hungarian Compromise until World War I. This port played an essential role in the contemporary Hungarian economy as it became an independent industrial center, one of the most important industrial cities of the Monarchy. The initial boost and then flourishing of Fiume in the second half of the 19th century was due to strategictransportation and economic policies. The improvement of the transportation routes crossing the mountains that isolate the city from the main area of Hungary increased the importance of Fiume and its surroundings, thus opening the way for development. As a result, the once insignificant port city became the rival of the main Austrian port of Trieste, gaining increased geographical functions as well. While initially it retained only transportation functions, by the turn of the century it became a noteworthy industrial, commercial, educational and administrative center. This expansion of functions greatly influenced the cityscape and the settlement structure. Around the web-like core of the city, new districts sprang up whose blueprint reflected a modern, conscious city planning effort. Thus, Fiume’s expanding functions resulted in apparent changes in the city structure. The present study describes the collective appearance of the above mentioned processes along with their interactions with one another, and it also discusses the role Fiume played in the contemporary Hungarian economic spatial structure.